Induction of adventitious rooting in stem cuttings of eastern redcedar (Juniperus virginiana L.) - Armbrust, Ryan W. (Kansas State University, 2020)
Eastern redcedar (Juniperus virginiana L.) is a vital component of windbreaks and conservation plantings across the Great Plains. Lack of management in rangeland has contributed to an exponential increase in establishment of eastern redcedar seedlings and conversion of land cover, decreasing productivity of rangeland while increasing fire risk. Eastern redcedar is dioecious (male and female individuals) so the selection and planting of seedless male specimens would be preferable to continuing mixed-sex plantings. Eastern redcedar does not reveal male or female cones until 10-15 years of age, making selection at the nursery stage (1-2 year-old seedlings) impossible. Grafted male specimens are available, but are not economical for low-cost conservation plant material use due to the comparatively high cost of grafting. If the rooting of stem cuttings from male specimens was made economically viable by increasing the success rate, then male eastern redcedars would be available for conservation purposes while reducing the threat of seedling establishment and vegetation cover conversion in adjacent rangelands. This study’s results indicate that stem cuttings of eastern redcedar can be induced to form adventitious roots using bottom heat and treatment with concentrated auxins (indole-3-butryic acid, IBA; and 1-napthaleneacetic acid, NAA), plant growth regulators that induce differentiation of plant tissue as roots. Rooting percentage was low (15-50%) compared to generally accepted rates for other horticultural species in the trade, but can potentially be improved through control of various environmental (i.e. water status, soil-induced stress) and genetic (i.e. provenance, form) factors in the stock plants from which cuttings are removed. Objectives for this research project were to: 1) Study the influence that root-promoting auxins have on stem cuttings of eastern redcedar, 2) Assess the establishment of eastern redcedars produced from rooted cuttings, as compared to traditionally-produced seedlings; and 3) Assess the growth form of rooted eastern redcedars for windbreak suitability.
Keywords: Adventitious roots; Cuttings; Juniperus virginiana; Eastern redcedar